TRANSFORMASI SOSIO-EKONOMI PRAJA MANGKUNEGARAN: PEMBANGUNAN PABRIK GULA COLOMADU OLEH MANGKUNEGARA IV (1861-1881) - Lucia Arter Lintang Gritantin (Journal of Innovation Research and Knowledge, 2025)
This study examines the influence of the construction of the Colomadu Sugar Factory on the social and economic structure of the Surakarta community, particularly within the Mangkunegaran Principality. Through historical methods including heuristics, criticism, interpretation, and historiography, it was found that KGPAA Mangkunegara IV's initiative to modernize the agrarian sector succeeded in shifting economic dependence from foreign entities to domestic independence. The transformation of the lungguh (appanage) land system into a salary system, along with the transition from rodi (corvée) labor to a wage system, marked a turning point for the emergence of a new middle class in Java.